Studi in silico: Screening Virtual Senyawa Triterpenoid pada Canophyllum inophyllum Sebagai Kandidat Inhibitor SARS-CoV-2 - Rena, Suci Ramda; Muttaqin, Afdhal; Fitriyani, Dian (Jurnal Fisika Unand, 2025)
This study aims to identify the potential of triterpenoid compounds from tamanu (Canophyllum inophyllum) as SARS-CoV-2 inhibitors through an in-silico approach using molecular docking. Ten triterpenoid compounds were selected and their binding affinity to the main protease (Mpro) of SARS-CoV-2 (PDB ID: 6W63) was tested. The results showed that four triterpenoid compounds, including oleanolic acid (-8.2 kcal/mol), friedelin (-8.2 kcal/mol), inophynone (-8.1 kcal/mol), and epifriedelanol (-8.2 kcal/mol) had lower binding affinity compared to the natural ligand (X77 -8.0 kcal/mol) and its reference ligand (paxlovid -7.7 kcal/mol), indicating a stronger interaction with the active site of the protein. Among the four candidates, only oleanolic acid forms hydrogen bonds with amino acid residues in the active site of the protein, which strengthens its potential role as a SARS-CoV-2 inhibitor. This finding suggests that these compounds, especially oleanolic acid, have the potential to be further developed as natural product-based Covid-19 therapies. This study provides an initial contribution to the exploration of natural products as a source of active compounds for the development of Covid-19 therapies through an in-silico approach.